Economic indicator system for adaptive monitoring of compound climate change risks - Zoe Qu; Wei Yang; Andrew Allison; Paula Blackett (Societal Impacts)
Climate change adaptation requires proactive development of adaptive planning strategies. To implement such strategies, it is crucial to identify indicators that can monitor and signal approaching adaptation thresholds. While existing research has focused on physical and hazard-based indicators, addressing social and economic indicators is essential for informed decision-making. This research aims to fill this gap by compiling 298 economic indicators across six categories: fiscal factors for central, regional, and local governments; financial system indicators; indicators for industries, businesses, and public organisations; and indicators for identifying socially vulnerable populations due to climate change. Derived from previous studies and the national climate change risk assessment framework, these indicators aim to provide policymakers at all levels and communities with a ready-to-use toolbox for monitoring climate change economic risks. Additionally, the research identifies measurable indicators as well as those that cannot currently be measured but could potentially be quantified. Future work involves further analysis and mapping of these indicators to form a cohesive set warning of the need for adaptation measures, aiming to equip decision-makers with tools to address the economic impacts of climate change.